Addressing human trafficking in the digital era: Amendments to the EU anti-trafficking directive: [Handel ludźmi w erze cyfrowej. Zmiany w dyrektywie UE w sprawie handlu ludźmi] (Studia Prawnicze / The Legal Studies, 2024)
This article examines the European Union’s legal response to the technological dimensions of the evolving crime of human trafficking, focusing on the digitalisation-related amendments to Directive 2011/36/EU on preventing and combating trafficking in human beings and protecting its victims. It explores the factors driving the technological expansion of this crime and the legislative changes introduced in response, while emphasizing the importance of addressing the demand-driven nature of trafficking as a key preventive measure. The paper aims to demonstrate how the European Union, as a law-based community, is responding to the challenges posed by the digitalisation of this crime by amending its key legal framework against human trafficking.[Przedstawiony artykuł stanowi analizę reakcji prawnej Unii Europejskiej na technologiczną ewolucję przestępstwa handlu ludźmi, koncentrując się na zmianach związanych z digitalizacją w dyrektywie 2011/36/UE w sprawie zapobiegania handlowi ludźmi i zwalczania tego procederu oraz ochrony ofiar. Artykuł bada czynniki napędzające technologiczny rozwój tego przestępstwa oraz wprowadzone w odpowiedzi zmiany legislacyjne, podkreślając znaczenie zwalczania popytu na usługi ofiar jako kluczowego środka prewencyjnego. Celem artykułu jest ukazanie, że Unia Europejska jako wspólnota oparta na prawie reaguje na wyzwania związane z cyfryzacją tego przestępstwa poprzez zmianę kluczowego, w walce z handlem ludźmi, aktu prawnego.]